Marijuana use modifies the association between heavy alcohol consumption and tobacco use patterns among US adults: Findings from Behavioral Risk Factor Surveillance System, 2020. (December 2022) - Osibogun, Olatokunbo; Erinoso, Olufemi; Gautam, Prem; Bursac, Zoran; Osibogun, Akin
Highlights: This study explored the association of heavy alcohol consumption with tobacco use patterns among US adults. Heavy alcohol consumption was associated with higher odds of current e-cigarette, cigarette & dual use. Associations were modified by past-month marijuana use. Stronger associations were observed in past-month marijuana non-users than in past-month marijuana users. Longitudinal research is needed to clarify results & implications for public health. Abstract: Objective: This study explored the associations of heavy alcohol consumption with current e-cigarette, cigarette and dual use of e-cigarettes and cigarettes among a nationally representative sample of adults in the United States (US), and if these associations are modified by marijuana use. Methods: Data from 157, 138 adults who participated in the 2020 Behavioral Risk Factor Surveillance System (BRFSS) were included in this cross-sectional analysis. Multinomial logistic regression was used to estimate the strength of the associations between heavy alcohol consumption (independent variable) and the tobacco use patterns (dependent variable, i.e., non-use, current e-cigarette use, current cigarette use and current dual use of e-cigarettes and cigarettes). We also assessed the interaction between past-month marijuana use and heavy alcohol consumption on the primary outcome. Results: After the adjustment for potential confounders, heavy alcohol consumption (relative to no heavy alcohol consumption) was associated with higher odds of current e-cigarette (3.91 [2.25–6.78]), cigarette (3.02 [2.28–3.99]) and dual (4.78 [3.25–7.01]) use. The test for interaction showed that the associations of heavy alcohol consumption with the tobacco use patterns were modified by past-month marijuana use (p < 0.05 for all groups), with associations being much stronger among past-month marijuana non-users. Conclusions: Heavy alcohol consumption is positively associated with current e-cigarette, cigarette, and dual use among US adults. Further, the findings indicate that these relationships are modified by past-month marijuana use. Longitudinal research is needed to explore the role of marijuana in the association of heavy alcohol consumption with current e-cigarette, cigarette and dual use among adults.